Acoustic Emission Mapping of Discharges in Spark Erosion Machining - Smith, Craig (My University, 2013)
Electrical discharge machining (EDM) is a non-conventional machining process utilizing a series of electrical discharges to melt and vaporize workpiece material. In a wire EDM configuration wire breakage is a limiting factor in the machining productivity during the machining of workpieces with varying heights. Present methods of estimating workpiece height on-line in an effort to optimize machining parameters monitor the electrical signals for changes which may not be completely indicative of a change in workpiece height. This thesis intends to utilize acoustic emission (AE) sensors as a method for mapping the discharge location in order to estimate the workpiece height. This represents a novel approach as acoustic emission testing, while prevalent in the process monitoring of numerous conventional machining processes has yet to be significantly studied in combination with EDM.
Another useful application of AE sensors with the EDM process under consideration is during the fast hole EDM process, where excessive wear is seen in the electrode causing true electrode length to remain uncertain. By using acoustic emission sensors to determine the true length of the electrode it could be possible to aid in the breakout detection of the electrode.
Keywords: Acoustic Emission (AE); Spark Erosion Machining; Electrical Discharge Machining (EDM); Mapping; Source Location; Manufacturing; Manufacturing